2004
DOI: 10.1177/0021934703259014
|View full text |Cite
|
Sign up to set email alerts
|

African American Intergender Relationships a Theoretical Exploration of Roles, Patriarchy, and Love

Abstract: Current expectations of men andwomen in society have undergone tremendous changes concerning roles and the expression of intimacy within intergender relationships. African American intergender relationships have not escaped these changes. Three theoretical perspectives are offered to enrich the discussion on African American intergender relationships: patriarchy, role, and love. This article posits that African American intergender relationships are defined within some particular significant parameters like pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 16 publications
(16 reference statements)
0
20
0
Order By: Relevance
“…Whereas all groups demonstrated some degree of gender difference, Black students were the only racial group in which women expressed significantly greater agreement with the statement ''I wish there were more opportunities for going on dates'' and men expressed significantly greater agreement with the statement ''Any kind of sexual activity is okay as long as both persons freely agree to it'' (results not shown). The conflicting attitudes of Black women and men may be reflective of a larger crisis within Black American gender relations (Hooks et al, 1995;Lawrence-Webb, Littlefield, & Okundaye, 2004;Patterson, 1993). In addition, prior research has indicated that Black women oppose interracial dating in part because they perceive Black men to have more opportunities for interracial dating: Interracial dating is seen as reducing the availability of partners for Black women (Childs, 2005), and quantitative data indicate that Black men's greater propensity for interracial marriage does in fact reduce the availability of (same-race) partners for Black women, especially among the highly educated (Crowder & Tolnay, 2000).…”
Section: The Context and Quality Of Intraand Interracial Relationshipsmentioning
confidence: 99%
“…Whereas all groups demonstrated some degree of gender difference, Black students were the only racial group in which women expressed significantly greater agreement with the statement ''I wish there were more opportunities for going on dates'' and men expressed significantly greater agreement with the statement ''Any kind of sexual activity is okay as long as both persons freely agree to it'' (results not shown). The conflicting attitudes of Black women and men may be reflective of a larger crisis within Black American gender relations (Hooks et al, 1995;Lawrence-Webb, Littlefield, & Okundaye, 2004;Patterson, 1993). In addition, prior research has indicated that Black women oppose interracial dating in part because they perceive Black men to have more opportunities for interracial dating: Interracial dating is seen as reducing the availability of partners for Black women (Childs, 2005), and quantitative data indicate that Black men's greater propensity for interracial marriage does in fact reduce the availability of (same-race) partners for Black women, especially among the highly educated (Crowder & Tolnay, 2000).…”
Section: The Context and Quality Of Intraand Interracial Relationshipsmentioning
confidence: 99%
“…The independent nature of these women may cause feelings of male inadequacy in the provider role, and create stress for men that could lead them to withdraw emotionally (Hill, 2001). These behaviors represent an unintentional gender role modeling for the younger generation (Lawrence-Webb, Littlefield, & Okundaye, 2004).…”
Section: Family Structurementioning
confidence: 99%
“…Education, race (1 = European American), age, years married, and parental status were included as control variables on the intercept and slope based on the previous literature (e.g., Etaugh and Spandikow 1981;Fan and Marini 2000;Lawrence-Webb et al 2004). All controls variables were time invariant and measured in 1980.…”
Section: Control Variablesmentioning
confidence: 99%